Effect of nano urea and micronutrient foliar application on growth and yield of Bhendi [Abelmoschus esculentus (L.) Moench] - Madhumitha, M; Sundaram, V (Plant Science Today, 2025)
A field experiment was conducted at the Department of Horticulture, Pandit Jawaharlal Nehru College of Agriculture and Research Institute, Karaikal, U.T. of Puducherry, on bhendi [Abelmoschus esculentus (L.) Moench] during summer 2024 to investigate the effects of nano urea and micronutrients spray on enhancing growth and productivity. The experiment was laid out in a Randomized Block Design (RBD) with 15 treatments, each replicated twice. The study materials included nano urea, 19:19:19 NPK water soluble fertilizer (WSF), zinc, boron and Arka vegetable special, besides recommended N, P, K fertilizers. Results revealed that the foliar application of Arka vegetable special 2 g L-1 as foliar spray thrice at 20th, 40th and 60th day of sowing along with Recommended Dose of fertilizers (RDF - 200:100:100 kg NPK ha-1) recorded significant reduction in days to flowering (33.40 days), enhanced plant growth with maximum plant height of 29.20 cm at first flowering and 131.30 cm at final harvest, increased number of primary branches at first flowering (2.50) and at final harvest (3.90), with shorter internode of 2.52 cm. Similar trends were also observed with respect to major yield attributes viz., fruit length (20.00 cm), fruit girth (7.20 cm), individual fruit weight (25.30 g), number of fruits plant-1 (49.50) and total yield (1.00 kg plant-1 and 20.60 t ha-1) were notably improved, reflecting a 55.47 % yield increase over the control (RDF). These findings underscore the efficacy of foliar supplementation of micronutrients in enhancing the growth and productivity of bhendi.